A matrix variate skew‐t distribution. Issue 1 (2nd May 2017) - Gallaugher, Michael P.B.; McNicholas, Paul D.
Abstract : Although there is ample work in the literature dealing with skewness in the multivariate setting, there is a relative paucity of work in the matrix variate paradigm. Such work is, for example, useful for modelling three‐way data. A matrix variate skew‐ t distribution is derived based on a mean‐variance matrix normal mixture. An expectation‐conditional maximization algorithm is developed for parameter estimation. Simulated data are used for illustration. Copyright © 2017 John Wiley & Sons, Ltd.